2018
DOI: 10.1007/s12687-018-0357-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and improving the implementation of a community-based hereditary cancer screening program

Abstract: Healthcare disparities exist in the provision of cancer genetic services including genetic counseling and testing related to BRCA1/2 mutations. To address this in a community health setting a screening tool was created to identify high-risk women. This study evaluates the implementation of the tool and identifies opportunities for improved cancer genetic screening, including regular clinician education. A mixed-method approach was used to evaluate clinician utilization of the screening tool at Planned Parentho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Telegenetics appointments were well received by patients and reduced barriers of conventional in‐person genetic counseling appointments such as lack of transportation, childcare, or time off work (Cohen et al., 2016 ; Greenberg et al., 2019 ; Hilgart et al., 2012 ; Joseph & Guerra, 2014 ; Joseph et al., 2017 ; Kinney et al., 2010 ; Komenaka et al., 2015 ; McCarthy et al., 2016 ; Rana et al., 2018 ; Sherman et al., 2013 ). Increased accessibility of genetic services is especially important among underserved populations, and data from the CH patient population demonstrated that telephone consultations are an effective and potentially more successful means of reaching these patients for genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Telegenetics appointments were well received by patients and reduced barriers of conventional in‐person genetic counseling appointments such as lack of transportation, childcare, or time off work (Cohen et al., 2016 ; Greenberg et al., 2019 ; Hilgart et al., 2012 ; Joseph & Guerra, 2014 ; Joseph et al., 2017 ; Kinney et al., 2010 ; Komenaka et al., 2015 ; McCarthy et al., 2016 ; Rana et al., 2018 ; Sherman et al., 2013 ). Increased accessibility of genetic services is especially important among underserved populations, and data from the CH patient population demonstrated that telephone consultations are an effective and potentially more successful means of reaching these patients for genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…From this, an education module was developed to improve clinician knowledge of cancer genetics and self-efficacy for connecting clients to genetic counseling and testing for HBOC; this module was then implemented and evaluated. 48 In the end, the education module was effective in improving knowledge and confidence among clinicians. Using implementation frameworks, 34 strategies 49 and measures 50 will further strengthen health disparities research in genomics, by providing standardized metrics and strategies for assessing use of genomic medicine across clinical and public health settings.…”
Section: Addressing Health Disparities Through Implementation Sciencementioning
confidence: 99%
“…Racial minority populations in the United States are disproportionately affected by these healthcare disparities (73). Consistent with these findings, multiple studies have documented disparities in access to genetic services for low-income and minority patients (36,53,63,65,69,119,126). Barriers include limitations in physicians' genetics knowledge, use of genetic testing, and referral to genetic services; availability and cost of services; lack of translation services; and failure of appropriate follow-up after testing or referral occurs.…”
Section: Equitymentioning
confidence: 71%
“…Barriers include limitations in physicians' genetics knowledge, use of genetic testing, and referral to genetic services; availability and cost of services; lack of translation services; and failure of appropriate follow-up after testing or referral occurs. Although clinic-based interventions can improve genetic assessment and referral rates (63,69), many of the barriers reflect underlying social determinants that constrain patient options (53).…”
Section: Equitymentioning
confidence: 99%